Cardiac arrhythmias in obstructive sleep apnea - Schweitzer, Pavol (Vnitřní lékařství, 2008)
Obstructive sleep apnea syndrome (OSA) is associated with different types of cardiac arrhythmias. The original studies, concentrated mostly on nocturnal brady- and tachyarrhythmias. More recent studies documented high prevalence of atrial fibrillati on (AF) and its association with obesity and other risk factors for AF. In addition, continuous positive airway pressure (CPAP) prevents recurrence of AF after cardioversion. In, OSA the highest risk for sudden death is at night in comparison to general population most of who die suddenly between six and noon. This observati on suggests that hypoxia or other nocturnal abnormality, trigger sudden death. An important recent finding is the beneficial effect of CPAP on sudden death. The role of pacing in OSA remains controversial. In general, pacemaker therapy is not indicated in patients with nocturnal bradyarrhythmias. However, some authors recommend pacing in those with severe nocturnal bradyarrhythmias not tolerating or not responding to CPAP. According to a recent study, 59% of patients with permanent pacemaker have OSA.
Keywords: Death, Sudden; fibrilace síní; obstrukční spánková apnoe; Sleep Apnea, Obstructive; lidé; Atrial Fibrillation; náhlá smrt; Continuous Positive Airway Pressure; elektrická defibrilace; Cardiac Pacing, Artificial; Humans; Electric Countershock; trvalý přetlak v dýchacích cestách; Arrhythmias, Cardiac; kardiostimulace umělá; srdeční arytmie